Probing into hinterland connectivity with a web of transport modes and logistics nodes: a case of Indian container ports - Deshmukh, Ajay; Song, Dong-Wook (Elsevier, 2024)
This article investigates the conceptual and empirical aspects of hinterland connectivity, focusing on container ports in India as a case study. It aims to clarify the complex and multidimensional nature of hinterland connectivity within the context of container ports by addressing a key conceptual issue. The study proposes that port-hinterland connectivity goes beyond direct links and emphasises the strategic relationships with key logistics centres in the hinterland. By employing centrality measures from social network analysis, the study evaluates the overall connectivity of Indian container ports, considering both direct and indirect connections from 2009 to 2021, to identify which ports have robust connections to key logistics centres. The results obtain by using eigenvector centrality reveal that an extensive hinterland network does not necessarily guarantee better hinterland connectivity for container ports. Additionally, the quality of connections, particularly to hubs with high betweenness centrality, is crucial for achieving a high degree of hinterland connectivity. These findings provide valuable policy insights, highlighting the importance of ports fostering closer relationships with key logistics hubs to effectively enhance their connectivity. Based on these findings, the paper offers policy recommendations for India aimed at improving connectivity in alignment with corresponding market shares. This research will serve as a foundation for further exploration of the interplay between port-hinterland connectivity and port market shares from a hinterland perspective, especially in a country like India, where hinterlands significantly overlap.
Keywords: Transport mode; Logistics node; Overlapped hinterland; Port-hinterland connectivity; Indian container port; Social network analysis; 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; Logistics & Transportation; 3304 Urban and regional planning; 3509 Transportation, logistics and supply chains